Biomarkers Associated With Leishmania infantum Exposure, Infection, and Disease in Dogs - Maia, Carla; Campino, Lenea (Frontiers in Cellular and Infection Microbiology, 2018)
Canine leishmaniosis (CanL) is a vector-borne disease caused by the protozoan Leishmania (Leishmania) infantum species (syn. L. (L.) chagasi species in the Americas) which is transmitted by the bite of a female phlebotomine sand fly. This parasitosis is endemic and affect millions of dogs in Asia, the Americas and the Mediterranean basin. Domestic dogs are the main hosts and the main reservoir hosts for human zoonotic leishmaniosis. The outcome of infection is a consequence of intricate interactions between the protozoan and the immunological and genetic background of the host. Clinical manifestations can range from subclinical infection to very severe disease. Early detection of infected dogs, their close surveillance and treatment are essential to control the dissemination of the parasite among other dogs, being also a pivotal element for the control of human zoonotic leishmaniosis. Hence, the identification of biomarkers for the confirmation of Leishmania infection, disease and determination of an appropriate treatment would represent an important tool to assist clinicians in diagnosis, monitoring and in giving a realistic prognosis to subclinical infected and sick dogs. Here, we review the recent advances in the identification of Leishmania infantum biomarkers, focusing on those related to parasite exposure, susceptibility to infection and disease development. Markers related to the pathogenesis of the disease and to monitoring the evolution of leishmaniosis and treatment outcome are also summarized. Data emphasizes the complexity of parasite-host interactions and that a single biomarker cannot be used alone for CanL diagnosis or prognosis. Nevertheless, results are encouraging and future research to explore the potential clinical application of biomarkers is warranted.